Relationship between Family History of Diabetes Mellitus and Gestational Diabetes Mellitus: A Meta-Analysis - Ammutammima, Ummu Fatihah; Tamtomo, Didik Gunawan; Murti, Bhisma (Indonesian Journal of Medicine, 2021)
Background: Gestational Diabetes Mellitus (GDM) is the most common metabolic disorder first diagnosed during pregnancy. According to the American Diabetes Association (ADA) in 2006, GDM occurred in 7% of pregnancies each year. Family history of diabetes is an important risk factor for GDM. The relationshipbetween family history of DM and GDM has been investigated in several primary studies with several contradictions in the outcome. Therefore, this study aimed to determine the relationship between family history of diabetes and GDM using a meta-analysis method.Subjects and Method: The meta-analysis was conducted by systematically reviewing articles published from 2007 to 2020 from the Pubmed, Google Scholar, Science Direct, and ResearchGate databases. The keywords were "Risk factor" OR "family history" OR "family history DM") AND "GDM" AND "cross sectional". The article search was carried out using PICO: the study population was pregnant women, the intervention/exposure was family history of DM, the comparison was no family history of DM, and the outcome was GDM. The article search was carried out for one month. The articles included in this study were full-text articles with a cross-sectional design. The articles were reviewed using the PRISMA flow diagram guidelines. This study used Revman 5.3 Software to analyze the articles.Results: Family history of DM increased the risk of Gestational Diabetes Mellitus (aOR= 2.02; 95% CI= 1.54 - 2.67; p<0.001). This study used 11 articles from Ethiopia, Cameroon, Peru, Iran, Pakistan, Malaysia, Kuwait, Saudi Arabia, and India.Conclusion: Family history of diabetes mellitus increases the risk of gestational diabetes mellitus.Keywords: Gestational diabetes mellitus, Family history of diabetesCorrespondence: Ummu fatihah Ammutammima. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: ummuftha64@gmail.com. Mobile: 081717252573.Indonesian Journal of Medicine (2021), 06(01): 71-81https://doi.org/10.26911/theijmed.2021.06.01.08.